“THE CONFRATERNITY AND THE BROTHERHOODS IN GUATEMALA (1993-2012)” - Hidalgo Torres, Antonio J. (2013)
The confraternity is a religious, social and cultural institution that has been present in Latin American Society’s history since the early colonial period. The confraternity also explicitly shows the combination of sacred and secular spheres of Latin American people. The article aims to show the effectiveness of this institution of the Catholic culture nowadays; the Archdiocese of Guatemala’s case is being taken as an example, for this confraternity has gained significant social institutionalization and legitimization. The situation of the Church will be analyzed, emphasizing the promotion of Catholic popular practices facing growing Protestant population. The confraternity will be defined in the context of Catholic jurisprudence. The study will make an in depth analysis into the administrative composition, the activities and the funding of the Archdiocese of Guatemala’s confraternity to finally culminate in a reflection on the elements that have made possible the durability of the confraternity in the Guatemalan people. It is expected that the article enriches, even though it is limitedly, the Guatemala´s culture and religiosity comprehension, and the Latin American, in general.